Light Regulates the Cytokinin-Dependent Cold Stress Responses in Arabidopsis - Prerostova, Sylva; Černý, Martin; Dobrev, Petre I.; Motyka, Vaclav; Hluskova, Lucia; Zupkova, Barbara; Gaudinova, Alena; Knirsch, Vojtech; Janda, Tibor; Brzobohatý, Bretislav; Vankova, Radomira (Frontiers in Plant Science, 2021)
To elucidate the effect of light intensity on the cold response (5 °C; 7 days) in Arabidopsis thaliana, we compared the following parameters under standard light (150 μmol m−2 s−1), low light (20 μmol m−2 s−1) and dark conditions: membrane damage, photosynthetic parameters, cytokinin oxidase/dehydrogenase (CKX) activity, phytohormone levels, transcription of selected stress- and hormone-related genes and proteome. The impact of cytokinins (CK), hormones directly interacting with the light signaling pathway, on cold responses was evaluated using transformants over-expressing CK biosynthetic gene isopentenyl transferase (DEX:IPT) or CK degradation gene HvCKX2 (DEX:CKX) under dexamethasone-inducible promoter. In wild-type plants, cold treatment under light conditions caused down-regulation of CKs (in shoots) and auxin, while abscisic acid (ABA), jasmonates and salicylic acid (SA) were up-regulated, especially under low light. Cold treatment in the dark strongly suppressed all phytohormones, except ABA. DEX:IPT plants showed enhanced stress tolerance associated with elevated CK and SA levels in shoots, and auxin in apices. Contrarily, DEX:CKX plants had weaker stress tolerance accompanied by lowered levels of CKs and auxins. Nevertheless, cold substantially diminished the impact from the inserted genes. Cold stress in dark minimized differences among the genotypes. Cold treatments in light strongly up-regulated stress marker genes RD29A, especially in roots, and CBF1-3 in shoots. Under control conditions, their levels were higher in DEX:CKX plants, but after 7-day stress, DEX:IPT plants exhibited the highest transcription. Transcription of genes related to CK metabolism and signaling showed a tendency to re-establish, at least partially, CK homeostasis in both transformants. Up-regulation of strigolactone-related genes in apices and leaves indicated their role in suppressing shoot growth. The analysis of leaf proteome revealed over 20,000 peptides, representing 3800 proteins and 2212 protein families (data available via ProteomeXchange, identifier PXD020480). Cold stress induced proteins involved in ABA and jasmonate metabolism, antioxidant enzymes and enzymes of flavonoid and glucosinolate biosynthesis. DEX:IPT plants up-regulated phospholipase D and MAP-kinase 4. Cold stress response at the proteome level was similar in all genotypes under optimal light intensity, differing significantly under low light. The data characterized the decisive effect of light–CK cross-talk in the regulation of cold stress responses.